Knowns and unknowns of bone metastases in patients with neuroendocrine neoplasms: A systematic review and meta-analysis. (March 2021) - Garcia-Torralba, Esmeralda; Spada, Francesca; Lim, Kok Haw Jonathan; Jacobs, Timothy; Barriuso, Jorge; Mansoor, Was; McNamara, Mairéad G.; Hubner, Richard A.; Manoharan, Prakash; Fazio, Nicola; Valle, Juan W.; Lamarca, Angela
Highlights: BMs in patients with NENs remain underdiagnosed and undertreated. PET/CT seemed to provide the highest sensitivity and specificity for BM detection. OS from time of BM diagnosis is long and hence, it is important to secure good QoL. Recommendations for management of BMs derived from current knowledge are provided. Prospective studies to identify biomarkers and improve management are required. Abstract: Objective: This systematic review and meta-analysis aimed to develop an evidence-based summary of current knowledge of bone metastases (BMs) in neuroendocrine neoplasms (NENs), inform diagnosis and treatment and standardise management between institutions. Methods: PubMed, Medline, EMBASE and meeting proceedings were searched for eligible studies reporting data on patients with BMs and NENs of any grade of differentiation and site; poorly-differentiated large/small cell lung cancer were excluded. Data were extracted and analysed using STATA v.12. Meta-analysis of proportions for calculation of estimated pooled prevalence of BM and calculation of weighted pooled frequency and weighted pooled mean for other variables of interest was performed . Results: A total of 149 studies met the eligibility criteria. Pooled prevalence of BMs was 18.4% (95% CI 15.4–21.5). BMs were mainly metachronous with initial diagnosis of NEN (61.2%) and predominantly osteoblastic; around 61% were multifocal, with a predisposition in axial skeleton. PET/CT seemed to provide (together with MRI) the highest sensitivity and specificity for BM detection. Almost half of patients (46.4%) reported BM-related symptoms: pain (66%) and skeletal-related events (SREs, fracture/spinal cord compression) (26.2%; weightedweighted mean time-to-SRE 9.9 months). Management of BMs was multimodal [bisphosphonates and bone-modifying agents (45.2%), external beam radiotherapy (34.9%), surgery (14.8%)] and supported by little evidence. Overall survival (OS) from the time of diagnosis of BMs was long [weighted mean 50.9 months (95% CI 40.0–61.9)]. Patients with BMs had shorter OS [48.8 months (95% CI 37.9–59.6)] compared to patients without BMs [87.4 months (95% CI 74.9–100.0); p = 0.001]. Poor performance status and BM-related symptoms were also associated with worse OS. Conclusions: BMs in patients with NENs remain underdiagnosed and undertreated. Recommendations for management of BMs derived from current knowledge are provided. Prospective studies to inform management are required.